MENURUNNYA ANGKA BUNUH DIRI DI JEPANG DITINJAU DARI KEBIJAKAN JISASTSU TAISAKU KIHON HOU - Muhammad Fadhli Dzil Ikram (Universitas Airlangga, 2022)
Suicide in some countries in the world is not a big problem. But in Japan, suicide is a very worrying social problem. Japan since 1998 experienced a very high increase in suicide rates. In 1998, suicide rates in Japan rose to above 30 thousand, after previously stabilizing at 20 thousand. This suicide rate lasts up to 5 years and shows no signs of decreasing. Therefore, in 2006, the Japanese government made Jisatsu Taisaku Kihon Hou or suicide measures basic law to reduce suicide rates. As a result, suicide rates declined in 2010, 4 years after the adoption of the suicide measures basic law. This research seeks to reveal the influence of Jisatsu Taisaku Kihon Hou by decreasing suicide rates in Japan. The object of research is various kinds of public documents relating to suicide in Japan in the period from 2006 to 2019. Using policy theory and literature, this study reveals the impact brought about by making suicide prevention laws on suicide rates that high in Japan since 1998. This research shows the efforts of the Japanese government to reduce suicide rates by using a variety of programs for all ages and to apply to all kinds of places. Thus, suicide rates can be reduced so that the suicide rate in Japan is no longer a social problem.